Three new species of the plant bug tribe Pilophorini from Japan (Hemiptera: Heteroptera: Miridae: Phylinae) - Yasunaga, Tomohide; Duwal, Ram Keshari (Zootaxa, 2025)
Three new species of the plant bug tribe Pilophorini, belonging to Hypseloecus Reuter, 1891 and Pilophorus Hahn, 1825 are described from Japan as new to science, based on recently accumulated specimens as well as field-based investigations. Hypseloecus fukutomii sp. nov. and H. tamaderai sp. nov. were confirmed to be associated with Loranthaceae mistletoes, Taxillus yadoriki and T. nigrans. Pilophorus reoi sp. nov., assumed to be a predator, was found from the shrub of a raspberry, Rubus sieboldii, on Amami-Oshima and Okino-Erabu Islands of the Ryukyus. Updated keys to the Japanese species of Hypseloecus and allied members of Pilophorus reoi sp. nov. are also provided.